Literature of Iranian Diaspora in the Context of “Cultural Translation”. Taghi Modarressi, Nasim Khaksar - Lilit Safrastyan (ՀՀ ԳԱԱ հրատ.)
Վերջին երկու տասնամյակում «մշակութային թարգմանություն» հայեցակարգը առանձնակի տեղ է զբաղեցնում մարդաբանական ուսումնասիրություններում: На протяжении последних двух десятилетий концепция "культурного перевода" занимает отдельное место в антропологических исследованиях. In the last two decades, the concept of "cultural translation" has had a special place in both anthropology and post-colonial studies.
Keywords: Literature; Language and Literature; Translation and interpretation